Development of Concept Map Assisted by Articulate Storyline 3 with Jigsaw Model on the Material of Islamic Kingdom in Indonesia - Zulkhaidah, Zulkhaidah; Kaksim, Kaksim; Junaidi, Juliandry Kurniawan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research was motivated by the fact that at SMAN 2 Batang Anai there was no development of web-based media, which resulted in students being less active in learning and less enthusiastic, because they still used teaching modules and printed books in the learning process. The aim of this research is to produce media in the form of concept maps. This research uses research and development methods or often called Research and Development (R&D). The results of this research are, the development of a concept map assisted by Articulate Storyline 3 with a jigsaw model on Islamic kingdom material in Indonesia which includes validation from experts, namely media expert validation of 95.71%, that the development of the concept map assisted by Articulate Storyline 3 meets the criteria for learning media. history that is valid and has been tested on students in class X.4 Phase E of SMAN 2 Batang Anai which is categorized as very practical.